A Semantic Analysis of Meaning Variations in the Song Lyrics by Selena Gomez - Siti Maria Ulfah; Umi Pujiati (Insan Kreasi Media, 2025)
Semantics is a branch of linguistics that studies meaning in language, both literal and implicit meanings that are shaped through context and the use of figurative language. In song lyrics, figurative meanings are often used to convey emotions and complex messages, allowing listeners to engage with the song more deeply. This study aims to identify the various types of meanings contained in song lyrics and to analyze the role of semantic aspects in constructing emotional and social messages. The research employs a qualitative descriptive method with a semantic analysis approach. The findings show that the lyrics of both songs contain various types of semantic meanings, including lexical meaning, grammatical meaning, contextual meaning, referential meaning, non-referential meaning, denotative meaning, connotative meaning, conceptual meaning, associative meaning, terminological meaning, idiomatic meaning, and proverbial meaning. These diverse meanings function to strengthen the delivery of themes such as self-empowerment and feelings of alienation or being forgotten, which are central to both songs. Thus, the semantic meanings within the lyrics not only enrich the content of the songs but also build an emotional connection between the singer and the listener.